Understanding decision making about major surgery: protocol for a qualitative study of shared decision making by high-risk patients and their clinical teams - Shaw, S; Hughes, G; Stephens, T; Pearse, R; Prowle, J; Ashcroft, RE; Avagliano, E; Day, J; Edsell, M; Edwards, J; Everest, L (BMJ Publishing Group, 2020)
Introduction Surgical treatments are being offered to more patients than ever before, and increasingly to high-risk patients (typically multimorbid and over 75). Shared decision making is seen as essential practice. However, little is currently known about what ‘good’ shared decision making involves nor how it applies in the context of surgery for high-risk patients. This new study aims to identify how high-risk patients, their families and clinical teams negotiate decision making for major surgery.